CHANGES IN LEARNING STYLE PREFERENCES OF POSTGRADUATES AFTER ENTERING A NEW LEARNING ENVIRONMENT - Yousafzai, Yasar Mehmood; Baseer, Najma; Fatima, Sadia; Ali, Asif; Shah, Inayat (Journal of Ayub Medical College Abbottabad, 2018)
Background: The aim of this study was to investigate whether the learning style preferences of post-graduate medical students change with time when they enter a new learning environment. The learning styles of post-graduate medical students from Pakistan were assessed on Kolb's Learning style inventory and prospectively monitored for any change when the students entered a degree program at the University of Glasgow. Methods: Medical doctors from Pakistan who joined post graduate program in Evidence Based Medicine and Health Professions Education participated in the study. Kolb's learning style inventory was used to evaluate the learning preferences. Learning styles were evaluated twice in the study, in the first term of the course and then at the end, with a time span of 7 months. Results: The predominant learning style preferences of students were '˜Assimilating' type, both at the beginning and at follow up. Some change in the learning style preferences of students was noted as 2/10 students moved to a different learning grid at follow-up. These results were assessed against gender, clinical and teaching experience using linear regression however no significant correlation was found. Conclusion: There was not enough evidence to suggest that learning style preferences of students change in a meaningful way after coming to a new learning environment. This study however, leads to a suggestion that further large sized longitudinal study should be done with enough statistical power to accept or reject the null hypothesis. Keywords: Learning Styles; Learning Style Inventory; Kolb, Experiential Learning Theory; Medical Education